Fault analysis to Determine Deformation History of Kubang Pasu Formation at South of UniMAP Stadium Hill, Ulu Pauh, Perlis, Malaysia - Adi Suryadi (UIR PRESS, 2016)
The Kubang Pasu Formation at South of UniMap Stadium Hill has suffered deformation that produced fault with various types and orientations. First deformation (ST1) is southeast – northwest were resulted normal, reverse, dextral and sinistral fault. At station 32, Reverse fault (N940E/480) from ST1 was cut by reverse fault (N480E/400) result of second deformation (ST2). Another cross cutting fault found at station 108, third deformation (ST3) with stress direction from northeast – southwest that produced reverse fault with strike direction N1340E and 680 of dip angle was cutting the reverse fault (N870E/660) from second deformation. The youngest deformation (ST4) has stress from east – west. At station 110, normal fault (N900E/300) is representing the youngest deformation was cutting the reverse fault (N1540E/520) from third deformation.